2017
DOI: 10.1038/s41550-017-0262-6
|View full text |Cite
|
Sign up to set email alerts
|

The independent pulsations of Jupiter’s northern and southern X-ray auroras

Abstract: Auroral hot spots are observed across the Universe at different scales 1 and mark the coupling between a surrounding plasma environment and an atmosphere. Within our own solar system, Jupiter possesses the only resolvable example of this large-scale energy transfer. Jupiter's Northern X-ray aurora is concentrated into a hot spot, which is located at the most poleward regions of the planet's aurora and pulses either periodically 2,3 or irregularly 4,5 . X-ray emission line spectra demonstrate that Jupiter's Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
103
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(116 citation statements)
references
References 41 publications
9
103
3
1
Order By: Relevance
“…We took the simulated X‐ray photon fluxes emitted from the in situ ion flux measurements at a 60° viewing angle to represent the latitudinal location of the observed northern X‐ray emissions (e.g., see Dunn et al, ; Gladstone et al, ). We multiplied these photon fluxes per cm 2 by the area of a typical dim X‐ray auroral region (e.g., time‐binned X‐ray projections in Dunn et al, ) to attain a total flux of photons from the aurora.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We took the simulated X‐ray photon fluxes emitted from the in situ ion flux measurements at a 60° viewing angle to represent the latitudinal location of the observed northern X‐ray emissions (e.g., see Dunn et al, ; Gladstone et al, ). We multiplied these photon fluxes per cm 2 by the area of a typical dim X‐ray auroral region (e.g., time‐binned X‐ray projections in Dunn et al, ) to attain a total flux of photons from the aurora.…”
Section: Resultsmentioning
confidence: 99%
“…The observed X‐ray aurora has shown a strange complexity. For example, in 30% of observations, the X‐ray aurora pulses with a regular period on the order of tens of minutes as reported by Dunn et al (; ), Gladstone et al (), and Jackman et al (); however, during other observations, the emission is either continuous or the pulses are erratic, with no clear periodic signature (Branduardi‐Raymont et al, ; Elsner et al, ). Therefore, when analyzing heavy ion measurements made by JEDI, it is important to consider that this emission is highly temporally and spatially variable and that the associated ion precipitation may also vary with time.…”
Section: Introductionmentioning
confidence: 86%
“…Kimura et al () traced the radio pulsation sources to the polar regions and suggested that they were associated with auroral field lines that map to the outer magnetosphere. QP pulsations in far ultraviolet and X‐ray emissions have been seen in the auroral regions, with periods often reported around 10 min but varying widely (Dunn et al, ; Gladstone et al, ; Nichols et al, ). QP pulsations have also been reported in the inner magnetosphere, for example, Glassmeier et al () found ∼10‐ to 20‐min magnetic pulsations in the Io plasma torus.…”
Section: Introductionmentioning
confidence: 99%
“…This hot spot has the periods of 12, 26, and 40–45 min, and its longitudinal and latitudinal position is similar to the IR polar patch in this study. From magnetospheric mapping, magnetopause reconnection or ultra low frequency waves driven by Kelvin Helmholts instabilities have been proposed as the mechanisms for precipitating charged particles to the hot spot (Dunn et al, , ; Gladstone et al, ; Kimura, Kraft, et al, ). These processes could be candidates that drive the pulsations observed in this study.…”
Section: Discussion and Summarymentioning
confidence: 99%